Oxygen reduction catalyst with controllable multi-level pore structure and preparation method and application thereof
By using organic magnesium salts and metal phthalocyanine to prepare oxygen reduction catalysts, forming micro-mesporous composite multi-stage pore structures and monodispersed metal atoms with high specific surface area, the problems of uncontrollable pore structures of existing materials and complex preparation methods are solved, and efficient oxygen reduction catalytic performance and good consistency are achieved.
Patent Information
- Application Number
- CN202410603039.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-05-15
AI Technical Summary
The existing transition metal-nitrogen-carbon material system has a single pore size and an uncontrollable pore structure, resulting in the inability to take into account the maximum exposure and efficient material transmission of the active site, which affects the catalytic performance. At the same time, the preparation method is cumbersome, time-consuming and poor consistency.
Using magnesium organic acid salt and metal phthalocyanine as raw materials, through Joule pulse heat treatment and acid solution etching, a micro-mesporous composite multi-stage pore structure with high specific surface area is formed, which promotes the exposure of active sites and reduces oxygen transmission resistance. At the same time, controllable rise and fall of millisecond-level Joule pulses is used to achieve monodispersed existence of metal atoms.
The high electrochemical active area and oxygen reduction half-wave potential of the oxygen reduction catalyst are achieved, which can cover the demand for oxygen transmission in various power generation conditions, and improve the consistency and application flexibility of the catalyst.
Smart Images

Figure CN118610487B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of new energy materials, and specifically relates to an oxygen reduction catalyst with a controllable multi-level pore structure and a preparation method and application thereof. Background Art
[0002] With the advancement of global energy transformation, hydrogen energy, as a secondary energy source with abundant sources, green and low carbon, and wide applications, can effectively solve the temporal and spatial instability and volatility of renewable energy such as photovoltaics and wind power, help the large-scale consumption of renewable energy, realize large-scale peak regulation of the power grid and cross-seasonal and cross-regional energy storage, and become a bridge connecting renewable energy and users.
[0003] Hydrogen fuel cells convert the chemical energy contained in hydrogen and oxygen directly into electrical energy through electrochemical reactions, breaking away from the Carnot cycle limitations of traditional heat engines. They are highly efficient energy conversion devices, but their high cost is a bottleneck that makes it difficult to achieve large-scale development. The resources of precious metals such as Pt, which are widely used in cathode oxygen reduction catalysts, are limited and expensive, making catalysts one of the most expensive materials in the core stack of fuel cells. Therefore, developing low-platinum loading or non-platinum material systems to reduce the cost of fuel cells is the future development direction. In recent years, transition metal-nitrogen-carbon materials have shown excellent performance in oxygen reduction reactions. Using them to replace existing Pt-based catalysts will greatly reduce costs, but transition metal-nitrogen-carbon material systems need to increase the density of active sites as much as possible. In the most ideal situation, monodispersed active metal sites with high atomic utilization are fully exposed under the conditions of a high specific surface area and rich microporous structure. The appropriate mesoporous structure enables oxygen to be smoothly transferred to the surface of the active sites under various working conditions, further improving the performance of fuel cells. At present, most transition metal-nitrogen-carbon material systems have a single pore size (mesopores or micropores) and an uncontrollable pore structure. The active sites cannot meet the requirements of maximum exposure and efficient material transfer efficiency, thus affecting their catalytic performance. In addition, the common preparation methods of transition metal-nitrogen-carbon materials are cumbersome, time-consuming, and have poor consistency.
[0004] Therefore, developing highly active oxygen reduction catalysts with controllable multi-level pore structures is an important direction for the development of fuel cells. Summary of the invention
[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes an oxygen reduction catalyst with a controllable multi-level pore structure and a preparation method and application thereof. The oxygen reduction catalyst has a micro-mesoporous composite multi-level pore structure with a high specific surface area, and the pore structure is adjustable and controllable, and contains metal atoms in a monodisperse form, so it has a high electrochemical active area and oxygen reduction half-wave potential.
[0006] The inventive concept of the present invention is: the present invention uses organic acid magnesium salt (such as magnesium citrate) and metal phthalocyanine as raw materials for preparation, and utilizes Me-N-rich x Cheap metal phthalocyanine at the (metal-nitrogen) site is used as the metal source, nitrogen source and partial carbon source, and organic acid magnesium salt is used as the carbon source. A large number of micropores are generated during the heat treatment process, and a micro-mesoporous composite multi-level pore structure with a high specific surface area is generated after etching with an acid solution, which promotes the exposure of active sites and reduces the resistance of oxygen transmission to the active sites. At the same time, the temperature is controllably raised and lowered by millisecond-level Joule pulses to achieve adjustable and controllable magnesium oxide particle size, inhibit the agglomeration of metal atoms under continuous high temperature, and allow the metal atoms to exist in a monodisperse form with high utilization rate. The construction of the multi-level composite pore structure and the metal atoms in a monodisperse form show good oxygen reduction activity in acidic electrolytes.
[0007] In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing an oxygen reduction catalyst, comprising the following steps:
[0008] (1) mixing an organic acid magnesium salt with metal phthalocyanine to obtain a mixed powder;
[0009] (2) subjecting the mixed powder to Joule pulse heat treatment under an inert atmosphere;
[0010] (3) Soaking the product treated in step (2) in an acid solution, stirring, filtering, and drying to obtain the oxygen reduction catalyst.
[0011] Specifically, when preparing the oxygen reduction catalyst of the present invention, the organic acid magnesium salt and the metal phthalocyanine are first mixed evenly, and the conductivity of the mixed precursor itself is used to perform Joule pulse heat treatment under an inert atmosphere; then the obtained product is immersed in an acid solution, and after drying, an oxygen reduction catalyst with a multi-level pore structure is obtained.
[0012] In this preparation process, on the one hand, metal phthalocyanine is used as a metal source, a nitrogen source and a partial carbon source, in which the metal atoms are coordinated with single atoms, and under the high temperature of millisecond-level Joule pulse heat, the agglomeration of metal atoms under continuous high temperature conditions is effectively avoided to form efficient M-Nx active sites, and the metal atoms exist in a monodisperse form with high atomic utilization, thereby improving the activity of the oxygen reduction catalyst; on the other hand, organic acid magnesium salt is used as a carbon source, and a large number of micropores (pore size less than 2nm) are generated after heat treatment, which greatly increases the specific surface area of the catalyst, is conducive to the full exposure of the surface active sites, and does not require much oxygen reaction. It is of great help in the working condition of high small current density; after the organic acid magnesium salt is subjected to Joule pulse heat treatment, a magnesium oxide template is generated in situ, and after being etched by an acid solution, mesopores (pore size is 2-50nm) are formed, which is beneficial to the exposure of active sites and allows oxygen to be smoothly transmitted to the active sites in the mesopores, especially in the working condition of high current density with a large demand for oxygen reaction, which can effectively improve the oxygen reduction activity; the combined effect of micropores and mesopores maximizes the exposure of active sites, reduces the oxygen mass transfer resistance, helps to smoothly transmit oxygen to the active sites in the pores, and can cover the oxygen transmission needs of various power generation conditions.
[0013] In addition, by using millisecond-level Joule pulse heating and cooling, the Joule heating parameters can be changed to achieve adjustable and controllable magnesium oxide particle size, making the application of the prepared catalyst more flexible and more consistent.
[0014] Preferably, in step (1), the metal phthalocyanine is selected from at least one of iron phthalocyanine, cobalt phthalocyanine, nickel phthalocyanine, copper phthalocyanine and zinc phthalocyanine.
[0015] Preferably, in step (1), the organic acid magnesium salt comprises magnesium citrate and / or a hydrate of magnesium citrate; further preferably, the organic acid magnesium salt is magnesium citrate nonahydrate.
[0016] Preferably, in step (1), the mass ratio of the organic acid magnesium salt to the metal phthalocyanine is (15-35):1; further preferably, the mass ratio of the organic acid magnesium salt to the metal phthalocyanine is (20-35):1.
[0017] Preferably, in step (1), the mixing method is grinding, and the grinding time is 10-30 minutes.
[0018] Preferably, in step (2), the process parameters of the Joule pulse heat treatment are: pulse current 100-300A, pulse number 2-6 times, pulse interval time 3-15s, cooling circulating water temperature 5-15°C.
[0019] Preferably, in step (2), the inert atmosphere is an argon atmosphere or a nitrogen atmosphere.
[0020] Preferably, in step (3), the acid solution comprises hydrochloric acid, and the concentration of the hydrochloric acid is 5-10 mol / L.
[0021] Preferably, in step (3), the stirring time is 8-24 hours, and the stirring speed is 150-300 rpm.
[0022] Preferably, in step (3), the drying temperature is 50-90° C., and the drying time is 8-24 hours.
[0023] A second aspect of the present invention provides an oxygen reduction catalyst prepared by the above-mentioned method for preparing the oxygen reduction catalyst.
[0024] Preferably, the oxygen reduction catalyst has a multi-level pore structure and contains metal single atom sites; the multi-level pore structure includes mesopores and micropores.
[0025] Specifically, the oxygen reduction catalyst of the present invention is a multi-level porous transition metal-based carbon material with micropores and mesopores. The multi-level pores can not only ensure that the reactant oxygen is smoothly transferred to the surface of the active site, but also maximize the exposure of the active sites, increase the effective active site density and the electrochemical active area, and are more conducive to improving the oxygen reduction half-wave potential and the electrochemical active area.
[0026] The third aspect of the present invention provides use of the above oxygen reduction catalyst.
[0027] Specifically, the application includes a fuel cell, which includes the above oxygen reduction catalyst.
[0028] Preferably, the oxygen reduction catalyst is used in an acidic electrolyte in a fuel cell.
[0029] Preferably, the acidic electrolyte is HClO 4 .
[0030] Preferably, the HClO 4 The concentration is 0.05-0.2mol / L.
[0031] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0032] (1) When preparing the oxygen reduction catalyst of the present invention, metal phthalocyanine is used as the metal source, nitrogen source and part of the carbon source, and with the help of millisecond Joule pulse heat, the agglomeration of metal atoms under continuous high temperature conditions is avoided, so that the metal atoms exist in a monodisperse form with high atomic utilization, thereby improving the activity of the oxygen reduction catalyst; magnesium citrate is used as the carbon source, and a large number of micropores are generated after heat treatment, which greatly increases the specific surface area of the catalyst and is conducive to the full exposure of the surface active sites; and the in-situ generated magnesium oxide template is etched with hydrochloric acid to generate mesopores, so that oxygen can be smoothly transmitted to the active sites in the mesopores; the multi-level pores of micropores and mesopores are combined to expose the active sites to the greatest extent, reduce the oxygen mass transfer resistance, and enable oxygen to be smoothly transmitted to the active sites in the pores, thereby achieving a high electrochemical active area and oxygen reduction half-wave potential of the oxygen reduction catalyst, and can meet the requirements of various power generation conditions for oxygen transmission.
[0033] (2) The oxygen reduction catalyst prepared by the present invention has a micro-mesoporous multi-level pore structure and contains metal atoms in a monodispersed form; therefore, it not only has excellent oxygen reduction catalytic performance, the oxygen reduction half-wave potential in an acidic electrolyte can reach 0.78V, but also has a high electrochemical active area, and the double-layer capacitance can reach 45.7mF cm -2 .
[0034] (3) The present invention utilizes millisecond-level Joule pulse heating and cooling, and can adjust and control the particle size of magnesium oxide by changing the Joule heating parameters, making the application of the prepared catalyst more flexible and more consistent. At the same time, no solvent is used in the entire preparation process, the preparation method is simple, environmentally friendly, and has good repeatability. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] Figure 1 TEM image of the oxygen reduction catalyst prepared in Example 1 of the present invention;
[0036] Figure 2 This is a TEM image of the oxygen reduction catalyst prepared in Comparative Example 1 of the present invention;
[0037] Figure 3 The nitrogen adsorption-desorption isotherm curve and the corresponding pore size distribution diagram of the oxygen reduction catalyst prepared in Example 3 of the present invention;
[0038] Figure 4 The wide-angle X-ray diffraction pattern of the oxygen reduction catalyst prepared in Example 2 of the present invention;
[0039] Figure 5 The oxygen reduction catalysts prepared in Examples 1-3 and Comparative Example 1 of the present invention were heated to 0.1 M HClO 4 Linear sweep voltammetric curve of oxygen reduction in;
[0040] Figure 6The oxygen reduction catalyst prepared in Example 1 of the present invention and Comparative Example 1 was heated to 0.1 M HClO 4 The double layer capacitance is calculated by the current density difference at 1.0 V. DETAILED DESCRIPTION
[0041] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0042] Example 1
[0043] A method for preparing an oxygen reduction catalyst comprises the following steps:
[0044] (1) 300 mg of magnesium citrate nonahydrate and 15 mg of iron phthalocyanine were placed in a mortar and ground thoroughly for 12 min to obtain a mixed powder;
[0045] (2) placing the mixed powder obtained in step (1) in a Joule heating device and performing Joule pulse heat treatment in an argon atmosphere, wherein: the pulse current is 180A, the number of pulses is 6, the pulse interval is 15s, and the cooling circulating water temperature is 10°C;
[0046] (3) The product treated in step (2) was immersed in a hydrochloric acid solution with a concentration of 8 mol / L, stirred at a speed of 200 rpm for 12 hours, then filtered to a pH value of 7, and then dried in a vacuum oven at 70° C. for 10 hours to obtain the oxygen reduction catalyst of this embodiment, recorded as FeNC.
[0047] Example 2
[0048] A method for preparing an oxygen reduction catalyst comprises the following steps:
[0049] (1) 360 mg of magnesium citrate nonahydrate and 12 mg of nickel phthalocyanine were placed in a mortar and ground thoroughly for 15 min to obtain a mixed powder;
[0050] (2) placing the mixed powder obtained in step (1) in a Joule heating device and performing Joule pulse heat treatment in an argon atmosphere, wherein: the pulse current is 220A, the number of pulses is 5, the pulse interval is 8s, and the cooling circulating water temperature is 6°C;
[0051] (3) The product treated in step (2) was immersed in a hydrochloric acid solution with a concentration of 5 mol / L, stirred at a speed of 250 rpm for 18 hours, then filtered to a pH value of 7, and then dried in a vacuum oven at 60° C. for 12 hours to obtain the oxygen reduction catalyst of this embodiment, which is recorded as NiNC.
[0052] Example 3
[0053] A method for preparing an oxygen reduction catalyst comprises the following steps:
[0054] (1) 200 mg of magnesium citrate nonahydrate, 3 mg of cobalt phthalocyanine and 3 mg of copper phthalocyanine were placed in a mortar and ground for 20 min to obtain a mixed powder;
[0055] (2) placing the mixed powder obtained in step (1) in a Joule heating device and performing Joule pulse heat treatment in an argon atmosphere, wherein: the pulse current is 250A, the number of pulses is 3, the pulse interval is 12s, and the cooling circulating water temperature is 12°C;
[0056] (3) The product treated in step (2) was immersed in a hydrochloric acid solution with a concentration of 10 mol / L, stirred at a speed of 150 rpm for 8 hours, then filtered until the pH value was 7, and then dried in a vacuum oven at 50° C. for 16 hours to obtain the oxygen reduction catalyst of this embodiment, which was recorded as NiCuNC.
[0057] Comparative Example 1
[0058] A method for preparing an oxygen reduction catalyst comprises the following steps:
[0059] (1) 100 mg of conductive carbon material XC-72R and 15 mg of iron phthalocyanine were placed in a mortar and ground for 12 min to obtain a mixed powder;
[0060] (2) placing the mixed powder obtained in step (1) in a Joule heating device and performing Joule pulse heat treatment in an argon atmosphere, wherein: the pulse current is 180A, the number of pulses is 6, the pulse interval is 15s, and the cooling circulating water temperature is 10°C;
[0061] (3) The product treated in step (2) was immersed in a hydrochloric acid solution with a concentration of 8 mol / L, stirred at a speed of 200 rpm for 12 hours, then filtered to a pH value of 7, and then dried in a vacuum oven at 70° C. for 10 hours to obtain the oxygen reduction catalyst of this comparative example, recorded as FeNC-XC72R.
[0062] The only difference between Comparative Example 1 and Example 1 is that Comparative Example 1 uses 100 mg of the conductive carbon material XC-72R to replace 300 mg of magnesium citrate nonahydrate in Example 1 (the conductive carbon material obtained after 300 mg of magnesium citrate nonahydrate is heat treated and etched with hydrochloric acid is about 100 mg).
[0063] Performance Testing
[0064] 1. Microstructure
[0065] Figure 1 TEM image of the oxygen reduction catalyst FeNC prepared in Example 1. Figure 1 It can be seen that the morphology of the catalyst FeNC also contains mesopores ( Figure 1 The white dots circled in A) and micropores ( Figure 1 The white dots circled in B) have a multi-level pore structure; and no obvious metal particles are observed, indicating that the rapid carbonization of iron phthalocyanine under severe thermal shock avoids the agglomeration of metal atoms under continuous high temperature conditions, and exists in the form of monodispersed metal atoms with high atomic utilization.
[0066] Figure 2 A and Figure 2 B are TEM images of the oxygen reduction catalyst FeNC-XC72R prepared in Comparative Example 1 at different magnifications. Figure 2 It can be seen that the catalyst FeNC-XC72R exists mainly in the form of micropores, indicating that magnesium citrate nonahydrate has a positive effect on the generation of mesopores.
[0067] The oxygen reduction catalyst NiCuNC prepared in Example 3 was subjected to nitrogen adsorption and desorption isotherms and corresponding pore size distribution diagrams. The test process was as follows: after degassing at 350°C for 8 hours, nitrogen was used as the adsorption gas, and appropriate nitrogen adsorption and desorption pressures were set to conduct adsorption and desorption experiments and record the curves. According to the amount of nitrogen adsorbed and desorbed, the BJH (Barrett-Joiner-Halenda) method for measuring the seepage properties of each pore in the porous medium was used to obtain the pore size distribution curve of the sample. The specific surface area of the material was calculated according to the Brunauer-Emmet-Teller (BET) equation. The testing instrument was ASAP 2020M of Mack Co., Ltd. of the United States.
[0068] Figure 3 The nitrogen adsorption-desorption isotherm of the oxygen reduction catalyst NiCuNC prepared in Example 3 ( Figure 3 A) and the corresponding pore size distribution diagram ( Figure 3B), where: the horizontal axis Relative Pressure represents the relative pressure, Pore Width represents the pore width; the vertical axis Quantity Adsorbed represents the adsorption amount. Figure 2 It can be seen from A that NiCuNC has obvious IV-type hysteresis characteristics, which is a typical nitrogen adsorption and desorption isotherm of multi-level porous materials. The pore size distribution diagram obtained according to the BJH model shows that Fe / N-HPC has a large number of micropores and mesopores below 10nm. This result is also consistent with Figure 1 The specific surface area of the material was calculated to be 1723 m according to the BET (Brunauer-Emmett-Teller) method. 2 / g, such a high specific surface area is due to the developed micro-mesoporous composite multi-level pore structure.
[0069] 2. Component Analysis
[0070] Figure 4 This is the wide-angle X-ray diffraction pattern of the oxygen reduction catalyst prepared in Example 2, wherein: the horizontal axis 2-Theta represents the diffraction angle 2θ, and the vertical axis Intensity represents the intensity of the diffraction peak. Figure 4 It can be seen that NiNC has carbon (002) diffraction peaks at around 22° and carbon (100) diffraction peaks at around 43°, and no diffraction peaks of metal nickel particles or nickel oxides, carbides or nitrides are found. This further confirms that the metal in the catalyst exists in atomic form.
[0071] 3. Oxygen reduction half-wave potential
[0072] The oxygen reduction performance of the oxygen reduction catalysts prepared in Examples 1-3 and Comparative Example 1 was tested in a three-electrode system. The test process was as follows: the oxygen reduction catalyst powders prepared in Examples 1-3 and Comparative Example 1-2 were dispersed in ethanol respectively, a proton conductor binder (5% Nafion solution) was added to prepare a catalyst ink (1 mL of the catalyst ink contained 20 μL of the proton conductor binder), and then ultrasonicated for 30 minutes. The ink was then dropped onto the surface of a platinum carbon electrode and naturally dried to form a catalyst film, which was used as a working electrode for testing. A platinum wire was used as a counter electrode, and a reversible hydrogen electrode was used as a reference electrode. The oxygen reduction performance of each oxygen reduction catalyst was tested in 0.1 mol / L HClO 4 The oxygen reduction half-wave potential of the oxygen reduction catalysts prepared in Examples 1-3 and Comparative Example 1 was 0.1 mol / L HClO 4 ) in the oxygen reduction linear sweep voltammetry curve (LSV spectrum) as shown in Figure 5As shown in the figure (the horizontal axis Potential represents voltage, and the vertical axis Current density represents current density), the corresponding oxygen reduction half-wave potential is shown in Table 1.
[0073] Table 1:
[0074] Oxygen reduction catalyst <![CDATA[Oxygen reduction half-wave potential (V) in 0.1 mol / L HClO 4 > Example 1 (FeNC) 0.78 Example 2 (NiNC) 0.75 Example 3 (NiCuNC) 0.76 Comparative Example 1 (FeNC-XC72R) 0.71
[0075] As shown in Table 1, the oxygen reduction catalyst prepared in Examples 1-3 has a high activity in an acidic electrolyte (0.1 mol / L HClO 4 ) has an oxygen reduction half-wave potential of 0.75-0.78 V, and has excellent oxygen reduction catalytic performance.
[0076] In Comparative Example 1, relative to Example 1, the conductive carbon material XC-72R is replaced with magnesium citrate nonahydrate, mainly forming micropores, and its oxygen reduction half-wave potential is only 0.71 V, and its oxygen reduction catalytic performance is far inferior to that of Example 1.
[0077] 4. Double layer capacitor
[0078] The oxygen reduction catalysts prepared in Example 1 and Comparative Example 1 were heated in 0.1 M HClO 4 The double layer capacitance (C dl ), the result is as follows Figure 6 As shown, where: the horizontal axis Scan rate represents the scan rate, and the vertical axis Current density represents the current density. Figure 6 It can be seen that the double-layer capacitance of FeNC prepared in Example 1 is 45.7 mF cm -2 , which is much higher than the double-layer capacitance of FeNC-XC72R prepared in Comparative Example 1, which is 28.0 mF cm -2 , indicating that the multi-level pore structure increases the exposure of active sites accessible to oxygen in FeNC, and its electrochemical area is significantly higher than that of FeNC-XC72R, which is mainly composed of micropores.
[0079] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A method for preparing an oxygen reduction catalyst, characterized in that: The following steps are involved: (1) mixing an organic acid magnesium salt with metal phthalocyanine to obtain a mixed powder; The metal phthalocyanine is selected from at least one of iron phthalocyanine, nickel phthalocyanine and copper phthalocyanine, and the organic acid magnesium salt includes magnesium citrate and / or a hydrate of magnesium citrate; (2) Under an inert atmosphere, subjecting the mixed powder to Joule pulse heat treatment; the process parameters of the Joule pulse heat treatment are: pulse current of 100-300A, number of pulses of 2-6 times, pulse interval of 3-15s, and cooling circulating water temperature of 5-15°C; (3) Soaking the product treated in step (2) in an acid solution, stirring, filtering, and drying to obtain the oxygen reduction catalyst.
2. The method for preparing an oxygen reduction catalyst according to claim 1, characterized in that: In step (1), the mass ratio of the organic acid magnesium salt to the metal phthalocyanine is (15-35):
1.
3. The method for preparing an oxygen reduction catalyst according to claim 1, characterized in that: In step (1), the mixing method is grinding, and the grinding time is 10-30 minutes.
4. The method for preparing an oxygen reduction catalyst according to claim 1, characterized in that: In step (2), the inert atmosphere is an argon atmosphere or a nitrogen atmosphere.
5. The method for preparing an oxygen reduction catalyst according to claim 1, characterized in that: In step (3), the acid solution includes hydrochloric acid, and the concentration of the hydrochloric acid is 5-10 mol / L.
6. An oxygen reduction catalyst, characterized in that The oxygen reduction catalyst is prepared by the preparation method of any one of claims 1 to 5, wherein the oxygen reduction catalyst has a multi-level pore structure and contains metal single atom sites; the multi-level pore structure includes mesopores and micropores.
7. A fuel cell, characterized in that: The fuel cell comprises the oxygen reduction catalyst according to claim 6.
Citation Information
Patent Citations
Oxygen reduction catalyst with high substance transfer rate and preparation method and application thereof
CN115101760A
Process for the preparation of nanocrystalline metal oxides
US20090325794A1